2017
DOI: 10.14740/jocmr2935w
|View full text |Cite
|
Sign up to set email alerts
|

Reported Exercise-Related Respiratory Symptoms and Exercise-Induced Bronchoconstriction in Asthmatic Children

Abstract: BackgroundUnlimited physical activity is one of the key issues of asthma control and management. We investigated how reliable reported exercise-related respiratory symptoms (ERRS) are in predicting exercise-induced bronchoconstriction (EIB) in asthmatic children.MethodsIn this prospective study, 179 asthmatic children aged 7 - 15 years were asked for specific questions on respiratory symptoms related to exercise and allocated into two groups according to whether they complained about symptoms. Group I (n = 134… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…As expected, EIB had an independent association with all three symptoms. However, exercise‐induced cough, wheeze, and shortness of breath have been found to be poor predictors for a diagnostic fall in FEV1 9,10 . Our observations support the concept that the symptoms are not specific for EIB, but also affected by ISO‐BMI and outdoor temperature.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As expected, EIB had an independent association with all three symptoms. However, exercise‐induced cough, wheeze, and shortness of breath have been found to be poor predictors for a diagnostic fall in FEV1 9,10 . Our observations support the concept that the symptoms are not specific for EIB, but also affected by ISO‐BMI and outdoor temperature.…”
Section: Discussionsupporting
confidence: 76%
“…Overweight has also been associated with poor physical fitness, 1,8 which can be one of the reasons for exercise‐induced respiratory symptoms eliciting asthma investigations. Exercise‐induced cough, wheeze, and shortness of breath are often interpreted as signs of asthma, but the correlation between the symptoms and actual bronchial hyper‐responsiveness has proven to be poor 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Thirty‐three studies investigated the prevalence of EIB in general population of children and adolescents. Ten studies reported the prevalence of EIB in child and adolescent athletes, and 23 studies in children and adolescents with asthma.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐three studies involving 2400 participants (1109 cases of EIB) reported the prevalence of EIB in children and adolescents with asthma. The diagnosis of asthma was made by physician in all but four studies, in which the diagnosis was based on symptom questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the incidence rate of exercise induced asthma in Iraqi girls aged between 12-16 years. A fall in PEFR readings greater than or equal to 15% regarded as asthmatic [19][20][21][22][23][24] . The severity of EIB cannot be predicated from the resting level of lung function, for this reason the exercise was chose as the indirect challenge to produce Bronchospasm.…”
Section: Discussionmentioning
confidence: 99%